The green mile [videorecording (DVD)] - Darabont, Frank; Hanks, Tom; Morse, David, 1953-; Cromwell, James; Hunt, Bonnie; Duncan, Michael Clarke; Jeter, Michael, 1952-2003; Greene, Graham, 1952-; Hutchison, Doug, 1960-; Rockwell, Sam; Stanton, Harry Dean, 1926-2017; King, Stephen, 1947- (Warner Home Video, 2000)
Death Row guards at a penitentiary, in the 1930's, have a moral dilemma with their job when they discover one of their prisoners, a convicted murderer, has a special gift.